2020
DOI: 10.3390/biomedicines8100433
|View full text |Cite
|
Sign up to set email alerts
|

PPARα Agonist Oral Therapy in Diabetic Retinopathy

Abstract: Diabetic retinopathy (DR) is an eye condition that develops after chronically poorly-managed diabetes, and is presently the main cause for blindness on a global scale. Current treatments for DR such as laser photocoagulation, topical injection of corticosteroids, intravitreal injection of anti-vascular endothelial growth factor (VEGF) agents and vitreoretinal surgery are only applicable at the late stages of DR and there are possibilities of significant adverse effects. Moreover, the forms of treatment availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 125 publications
(152 reference statements)
3
33
0
Order By: Relevance
“…Then, we examined expressions of PPARα downstream genes in mice ( Figure A4 ). The retina and the liver were used as expected target sites, in that the retina is our region of interest and the liver has been widely known to be associated with fenofibrate-related PPARα activation [ 31 , 32 , 33 ]. PPARα downstream genes such as Fgf21 and Acox1 were significantly upregulated in the fenofibrate-administered liver, compared with those in the vehicle-administered liver ( Figure A4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, we examined expressions of PPARα downstream genes in mice ( Figure A4 ). The retina and the liver were used as expected target sites, in that the retina is our region of interest and the liver has been widely known to be associated with fenofibrate-related PPARα activation [ 31 , 32 , 33 ]. PPARα downstream genes such as Fgf21 and Acox1 were significantly upregulated in the fenofibrate-administered liver, compared with those in the vehicle-administered liver ( Figure A4 ).…”
Section: Resultsmentioning
confidence: 99%
“…FGF21 exerts a therapeutic effect on glucose and lipid metabolism in mice [ 50 ]. Therefore, a phase 2B clinical trial has been investigated to examine whether pegbelfermin (a novel long-acting FGF21) has therapeutic effects on nonalcoholic fatty liver disease (NAFLD) and nonalcoholic steatohepatitis (NASH) [ 31 ]. A previous study demonstrated that FGF21 had a synergistic effect with insulin on glucose absorption that is in accordance with enhanced Glut1 expression [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Next, the liver was targeted as it has been known as a region for pemafibrate-induced PPARα activation [24,38,39]. The livers in pemafibrate-administered UCCAO-operated mice seemed larger than those in PBS-administered UCCAO-operated mice while we collected the samples.…”
Section: Induction Of Pparα Target Genes By Pemafibrate Administration In a Mouse Model Of Uccao-induced Retinal Ischemiamentioning
confidence: 99%
“…Peroxisome proliferator-activated receptor alpha (PPARα) is a well-known drug against hyperlipidemia. This agent can potentially reduce triglyceride levels and increase high-density lipoprotein cholesterol (HDL-C) levels [24]. The Fenofibrate Intervention and Event Lowering in Diabetes (FIELD) and The Action to Control Cardiovascular Risk in Diabetes (ACCORD) eye studies showed that fenofibrate, a well-known PPARα agonist, reduced the need for laser therapy and progression of diabetic retinopathy [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…It is a remarkable novelty of our present study that BGP-15 is able to counteract the detrimental effect of long-term diabetes on the functioning of the retina of ZDF rats. Such retinal protection in diabetes is usually seen in case of neuropeptides, trophic factors, antioxidants, or in case of agents with anti-inflammatory action (Varga et al, 2011;Varga et al, 2013;Varga et al, 2017;Tomita et al, 2020). Although BGP is not a neuropeptide, nor a trophic factor, it might exert some antioxidant or anti-inflammatory properties on the retina as described before on non-retinal cell lines (Sumegi et al, 2017).…”
Section: Discussionmentioning
confidence: 93%